The Regulation of Articles on State Institutional Insults to The Right to Freedom of Expression in Indonesia: A Critical Review - Wiwin; H. Syafa’at Anugrah Pradana; Muhammad Imam Dhiya’ul Haq (Jurnal Mulawarman Law Review, 2023)
This study examines the problematic regulation of articles of contempt of state institutions in Law No. 1 of 2023 concerning the Criminal Code on the right to freedom of opinion in Indonesia. This type of research is normative legal research that uses a statute, analytical, and conceptual approach. The results of this study show that juridically formal insults to state institutions (President, MPR, DPR, DPD, MA, and MK) are regulated in Article 240 and Article 241 of Law No. 1 of 2023 concerning the Criminal Code as complaint offenses. The existence of articles of contempt of state institutions has negative implications for the right to freedom of opinion if reviewed using the legal system theory with the concept of three elements of the legal system. In legal substance, the article of insult to state institutions is multi-interpretive because there is no clear and concrete distinction between insult and criticism. In legal structure, the article of contempt of state institutions has the potential to be misused because there are power relations both structurally and functionally between law enforcement and state institutions; and (3) legal culture, standardization of articles of insult to state institutions has the potential to degrade the pluralism of habits in society in opinion and expression.